An Analysis of Poverty among the Poor using the Poverty Depth Measure - Dunga, Steven Henry (International Journal of Economics and Financial Issues, 2024)
There are multiple measures that are used to determine the poor households, however, within the households below the poverty threshold, there are differences that exist among them. This paper explores poverty in South Africa using the poverty depth measure, which refers to the extent to which the income of the poor falls below the poverty line. The paper presents a succinct conceptualisation of poverty and the income poverty line measurement, and then goes on to examine the various ways in which poverty depth can be measured. The paper provides a comprehensive review of the literature on poverty gap and introduces the concept of poverty depth. The literature review shows that there are weaknesses in the poverty gap as traditionally conceived. A calculation of a poverty depth is done and an analysis of the determinants of poverty gap using an ordinary least squares (OLS) regression is conducted. The results show that the head of household’s characteristics such as gender, employment status and marital status are significant in explaining the variation in the poverty depth. The paper reveals that the poor are different in their circumstances and recommends targeted interventions in dealing with poverty at household level.